Effect of Fluctuating Aerosol Concentrations on the Aerosol Distributions in a Turbulent Jet - Hailin Yang; Jianzhong Lin; Tatleung Chan (Aerosol and Air Quality Research)
Abstract We apply the Reynolds averaging method to derive the averaged particle general dynamic equation (APGDE), which models the effect of fluctuations in aerosol concentrations on coagulation, referred to as the fluctuating coagulation term (FCT), based on the turbulent kinetic energy. The APGDE is numerically solved using the Taylor-series expansion method of moments for a turbulent jet; the equation is then validated by comparing some of the results with experimental values. Obtaining the distribution and evolution of the aerosol particle number concentration, mass concentration, mean diameter and geometric standard deviation both when the FCT is incorporated and when it is excluded, we find that the contribution of fluctuating concentrations to the coagulation becomes a factor when x/D = 5 and reaches a stable state when x/D = 20. When the FCT is considered, the number concentration, mean diameter and geometric standard deviation are clearly lower, larger and greater, respectively. The fluctuating concentrations intensify the coagulation, reduce the number concentration and increase the mean diameter. Therefore, such fluctuations in a turbulent jet cannot be neglected.